Does Green Accounting Matter for Financial Performance? Evidence from the Indonesia Mining Sector - Setiawan, Jodi; Diantimala, Yossi; Lautania, Maya Febrianty; Sayuthi, Sayuthi (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
This study examines the influence of green accountingenvironmental cost, environmental disclosure, and environmental performanceon the financial performance of companies in the mining sector. The population were mining companies listed on the Indonesia Stock Exchange from 2020 to 2023. The samples were selected using the purposive technique and the number of observations is 144 firm-years. Using themultiple regression method, this study revealed that green accounting positively affects thefinancial performance of the sample companies. Disclosure and environmental performance positively impact financial performance, while the effect of environmental costs on financial performance is not significant.